6 - Quality Assurance in Ethiopian Higher Education: Boon or Bandwagon in Light of Quality Improvement? - Tefera Tadesse (Journal of Higher Education in Africa, 2014)
Quality assurance has become a global issue crossing the cultural contexts of many higher education systems. However, questions still remain whether this notion underpins deeper quality improvement in instructional practice and student learning outcomes. In Africa, where there are rapidly growing and diversified higher education systems, the need to assure quality through external examiners, audits, subject reviews or benchmarking is evident, but it is not clear if quality and standards of education are improved as a con- sequence. This study examines whether the process and contents of quality assurance constitute a substantial means by which Ethiopian higher learning institutions improve the quality of teaching and learning. It also outlines the consequences of quality assurance and its associated factors. The study employed an evaluative case study that draws on a critical (emancipatory) paradigm of evaluation and reflective judgement, viewing through Perellon’s (2007) conceptual framework. Results suggest the presence of some misalign- ment and inherent methodological flaws; and these have brought only partial benefits, and some unintended ill-effects. The root causes of these results, as illustrated in this article, are that there is a lack of primary focus and holistic thinking in a sense to effect deeper improvement, and a likelihood of hopping on a quality assurance bandwagon. This article offers a perspective on what must be done to bridge the prevailing gaps in quality assurance functions, and build a culture of quality to improve current practices.